La consolazione di Dio nelle prove del ministero exempla in 2 Cor. 1, 3–11 - Iacoviello, Gildo (Collectanea Philologica, 2016)
In the following article we have tried to analyze the consolation of God in the Pauline ministry tests. The reason that prompted me to address the topic of consolation of God, finds its explanation in the fact that too often we focus on the sufferings of this time without cast an eye over a horizon of hope. The works we have examined could be a source of consolation for the man who is living moments of trial. It is processed in the following way: First of all, it has made an etymological study of two terms: affliction and consolation, trying to see the various facets of Jewish antiquity, and in the texts of Sacred Scripture, even with short references to classical Greek. Later it saw the word in the Old and New Testament. Then, after a brief summary of the Second Epistle to the Corinthians, it analyzed the passage 2 Cor. 1.3 to 11, which has been the subject of study and then move on to some issues, deepen through study of some authors who have addressed the issue. Particular attention was given to the sufferings of Christ that Paul experienced in his apostolate and their saving power for the believer.